Increased Environmental Awareness of Flooding through Public Activation Using Geographic Information System (GIS) and Community Video - Taibe, Patmawaty; Yuniarti, Kwartarini Wahyu (Faculty of Psychology, Universitas Surabaya, 2012)
This research was devoted to discover the roles of SIG outputs and community empowerment through community video to increase environmental awareness of disastrous flood. 60 research participants or subjects from 14 to 17 years old were representatives of 10 high schools in Sintang city and resided along Kapuas and Melawi riverbanks. The approach used in this research was action research – a measurement employing environmental awareness scales in two aspects, they were, attitudes and intentions during pre- and post- community video workshops on both control and experiment groups. The t-Test results during pre-test reflected the equivalence between control and experiment groups (attitudes .233 < .05 and intentions .136 < .05,). The Anova results confirmed that intervention was significantly influential towards the increased environmental awareness on experiment group (attitudes F=37.543, R-square .493 and intentions F=31.589, R- square .450). Penelitian ini bertujuan untuk mengetahui peranan output SIG dan pemberdayaan masyarakat melalui video komunitas dalam peningkatan kesadaran lingkungan terhadap bencana banjir. Partisipan penelitian sebanyak 60 subjek berumur 14-17 tahun merupakan perwakilan siswa dari 10 sekolah menengah atas di kota Sintang dan bertempat tinggal di pinggir sungai Kapuas dan Melawi. Pendekatan penelitian menggunakan pendekatan action research, pengukuran menggunakan skala kesadaran lingkungan dengan mengukur dua aspek yakni sikap dan keinginan/niat dan dilakukan sebelum dan sesudah workshop video komunitas pada kelompok kontrol dan kelompok eksperimen. Hasil t-Test saat pretest menunjukkan kesetaraan antara kelompok kontrol dan eksperimen (sikap .233 < .05 dan keinginan .136 < .05,). Hasil Anova menunjukkan intervensi memiliki pengaruh yang signifikan terhadap peningkatan kesadaran lingkungan pada kelompok eksperimen (sikap F=37.543, R-square .493 dan keinginan F=31.589, R-square .450).